Studi Komparasi Penggunaan Strategi Picture and Picture dengan Make A Match Terhadap Hasil Belajar IPA Kelas II Madrasah Ibtidaiyah Muhammadiyah Program Khusus Kartasura Tahun 2015/2016 - Sucahyo, Muhammad (2016)
This study aims to determine (1) the difference influence strategy picture and picture to make a match on learning outcomes IPA Class II MIM PK Kartasura, (2) a better effect between use of strategy picture and picture to make a match to obtain the results to learn science class II MIM PK Kartasura. This type of research is quantitative research experiment. The subject of this research class II B and class II C in MIM PK Kartasura year 2015/2016. The technique of collecting data is test and documentation.. Technique were analyzed using t tests were preceded by the prerequisite test analysis, the homogeneity test and test for normality. Based on the results of data analysis with significance level of 5% obtained ttest> t table, namely 2,213> 2,000 with the average value of learning outcomes of class II B is greater than class II C MIM PK Kartasura, ie 89.02> 82.16. The conclusion of this study are as follows: (1) There are differences in the effect of the strategy picture and picture to make a match the learning outcomes of class II IPA Muhammadiyah Islamic Elementary School Special Program Kartasura year 2015/2016. (2) Implementation of the strategy picture and picture greater influence than the strategy make a match the learning outcomes of class II IPA Muhammadiyah Islamic Elementary School Special Program Kartasura year 2015/2016.